Prognostic Value of MicroRNA-203a Expression in Breast Cancer - Costa Gomes, B (2018)
Tumor heterogeneity and the poor outcome of breast cancer (BC) patients have led researchers to define new markers of this disease. In recent years, microRNA expression patterns have proven to be valuable disease indicators. The level of miR-203a, in particular, was shown to be altered in different types of cancer. The objective of the present study was to assess the relationship between miR-203a expression and clinicopathological features of BC in a Portuguese cohort. The expression levels of miR‑203a were analyzed in 109 formalin‑fixed paraffin-embedded paired normal and tumor tissue samples. Significant overexpression of miR‑203a in the tumor tissues was found (1.7-fold higher) compared to the expression in the normal adjacent tissues (p=0.003). In addition, several clinicopathological characteristics presented an association with higher miR-203a expression levels. Tumors with diameter ≤18.5 mm (1.5-fold; p=0.019), tumors positive for estrogen receptor (fold-change, 1.71; p=0.042), progesterone receptor (fold-change, 1.50; p=0.046) and negative for HER2 (fold-change, 1.50; p=0.016) and high Ki-67 index (fold-change, 2.60; p=0.024) presented a significant difference in miR-203a expression compared with adjacent normal tissues. Tumors without invasion of lymph nodes also presented higher expression of miR-203a (fold-change, 2.40; p=0.004). With regard to histological classification, ductal carcinomas in situ (fold-change, 2.20; p=0.028) and invasive carcinoma NOS (fold-change, 1.71; p=0.009) displayed significantly higher expression of miR-203a. Moreover, we found a significant downregulation of miR-203a with increased stage in invasive lobular carcinomas, suggesting that miR-203a could represent a potential marker to discriminate stages in invasive lobular carcinomas.